Guests at God's wedding : celebrating Kartik among the women of Benares - Pintchman, Tracy (State University of New York Press, 2005)
Tracy Pintchman explores how women who perform Kartik puja understand and celebrate both Kartik and Krishna in ways that are linked to the desires, hopes, fears, and social realities characteristic of many Hindu women living in the rather conservative social milieu of this region."--Jacket.